All-inorganic perovskite CsPbBr3-based self-powered light-emitting photodetectors with ZnO hollow balls as an ultraviolet response center. Issue 19 (4th May 2018) - Song, Zehao; Zhou, Hai; Gui, Pengbin; Yang, Xiaohan; Liu, Ronghuan; Ma, Guokun; Wang, Hao; Fang, Guojia
Abstract : Self-powered light-emitting photodetectors (SLEPs) can simultaneously transmit and receive information using light, offering huge potential for applications in interactive communication systems. Abstract : Self-powered light-emitting photodetectors (SLEPs) can simultaneously transmit and receive information using light, offering huge potential for applications in interactive communication systems. However, high-performance SLEPs are very hard to achieve due to the seriously contradictory principles of carrier transport in SLEPs. In this study, a novel structure based on a ZnO hollow ball/CsPbBr3 heterojunction, in which ZnO hollow balls function as an ultraviolet (UV) response center and CsPbBr3 is designed to be a green light-emitting material, is reported as a high-performance SLEP. Since the ZnO hollow balls have superior light trapping characteristics for UV light, the device shows a huge UV response with the on/off ratio and detectivity up to 16 527 and 2.4 × 10 13 Jones, respectively. Moreover, it displays blue emission with a low threshold voltage because of CsPbBr3 . Compared with the traditional ZnO/GaN structure devices, the device showed enhanced dual-functional performance at various wavelengths due to the insertion of CsPbBr3, which resulted in a better contact interface and green-light emission center. Our structure separating the light-responsive and emitting active regions avoids the contradictory principles of carrier transport, which may provide new access to gain high-performance dual-functional devices.